Eight new species of Ptenidiini and Discheramocephalini (Coleoptera: Ptiliidae) from Ecuador - Darby, Michael (European Journal of Taxonomy, 2020)
Eight new species of Ecuadorian Ptiliidae are described and figured: Nossidium harrietae sp. nov., Ptenidium robustum sp. nov., P. tauriforme sp. nov., P. triangulum sp. nov., Notoptenidium brunneum sp. nov., Americoptilium nigrescens sp. nov., Discheramocephalus nigerrimus sp. nov. and D. striatus sp. nov. The insects were collected by J. McClarin, 2017–2018, in the Napo Province to the southeast of the capital Quito.